Transcription Factor GATA4 Regulates Cell Type–Specific Splicing Through Direct Interaction With RNA in Human Induced Pluripotent Stem Cell–Derived Cardiac Progenitors. Issue 10 (8th August 2022) - Zhu, Lili; Choudhary, Krishna; Gonzalez-Teran, Barbara; Ang, Yen-Sin; Thomas, Reuben; Stone, Nicole R.; Liu, Lei; Zhou, Ping; Zhu, Chenchen; Ruan, Hongmei; Huang, Yu; Jin, Shibo; et al.
Abstract : Background: GATA4 (GATA-binding protein 4), a zinc finger–containing, DNA-binding transcription factor, is essential for normal cardiac development and homeostasis in mice and humans, and mutations in this gene have been reported in human heart defects. Defects in alternative splicing are associated with many heart diseases, yet relatively little is known about how cell type– or cell state–specific alternative splicing is achieved in the heart. Here, we show that GATA4 regulates cell type–specific splicing through direct interaction with RNA and the spliceosome in human induced pluripotent stem cell–derived cardiac progenitors. Methods: We leveraged a combination of unbiased approaches including affinity purification of GATA4 and mass spectrometry, enhanced cross-linking with immunoprecipitation, electrophoretic mobility shift assays, in vitro splicing assays, and unbiased transcriptomic analysis to uncover GATA4's novel function as a splicing regulator in human induced pluripotent stem cell–derived cardiac progenitors. Results: We found that GATA4 interacts with many members of the spliceosome complex in human induced pluripotent stem cell–derived cardiac progenitors. Enhanced cross-linking with immunoprecipitation demonstrated that GATA4 also directly binds to a large number of mRNAs through defined RNA motifs in a sequence-specific manner. In vitro splicing assays indicated that GATA4 regulates alternative splicing through direct RNA binding, resulting in functionally distinct protein products. Correspondingly, knockdown of GATA4 in human induced pluripotent stem cell–derived cardiac progenitors resulted in differential alternative splicing of genes involved in cytoskeleton organization and calcium ion import, with functional consequences associated with the protein isoforms. Conclusions: This study shows that in addition to its well described transcriptional function, GATA4 interacts with members of the spliceosome complex and regulates cell type–specific alternative splicing via sequence-specific interactions with RNA. Several genes that have splicing regulated by GATA4 have functional consequences and many are associated with dilated cardiomyopathy, suggesting a novel role for GATA4 in achieving the necessary cardiac proteome in normal and stress-responsive conditions.